2021
DOI: 10.1038/s41416-021-01552-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with the pharmaceutical industry and the practice, knowledge and beliefs of medical oncologists and clinical haematologists: a systematic review

Abstract: Background: No previous review has assessed the extent and effect of industry interactions on medical oncologists and haematologists specifically.Methods: A systematic review investigated interactions with the pharmaceutical industry and how these might affect the clinical practice, knowledge and beliefs of cancer physicians. MEDLINE, Embase, PsycINFO and Web of Science Core Collection databases were searched from inception to February, 2021.Results: Twenty-nine cross-sectional and two cohort studies met the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Since the COI of CPG authors have been reported in multiple countries (20)(21)(22)(23)(24)(25)(26), comparing directly how financial and nonfinancial COI are managed in different countries is important for all stakeholders, including health care professionals, patients, and CPG authors. However, our previous study has been the only study that evaluated the financial COI of CPG authors in both Japan and the US, or nonfinancial COI by self-citation rates in CPGs (10).…”
Section: Introductionmentioning
confidence: 99%
“…Since the COI of CPG authors have been reported in multiple countries (20)(21)(22)(23)(24)(25)(26), comparing directly how financial and nonfinancial COI are managed in different countries is important for all stakeholders, including health care professionals, patients, and CPG authors. However, our previous study has been the only study that evaluated the financial COI of CPG authors in both Japan and the US, or nonfinancial COI by self-citation rates in CPGs (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike payments for clinical trials and research, personal payments such as lecturing reimbursement, consulting payments, and meal and beverages may undermine patient trust and influence physicians' treatment choices. [6][7][8][9][10][11] As oncologists and hematologists have been increasingly targeted by pharmaceutical companies over the past few years mainly reported by studies in the United States, [12][13][14] it is particularly important to properly manage financial conflicts of interest (FCOI) in order to prevent undue influence on patient care by financial interests from pharmaceutical companies and to build patients' trust among the PHOs. 15 This trend in the financial relationship between PHOs and pharmaceutical companies could also apply to the situation in Japan, the third world-largest pharmaceutical market.…”
mentioning
confidence: 99%
“…While the trend was similar for both medical and hematological oncologists, the overall payments made to medical oncologists was relatively higher across all the years. Prior research has shown that oncological physicians in the US receive non-research nancial payments from pharmaceutical drug and medical device manufacturers at a prevalence of 63% 10 , and our ndings reveal that the majority of the overall sum goes to medical oncologists. Our analysis revealed that the majority of the payments (over 80%) were in the $0 to $50 range suggesting that most of the individual payments made were relatively small.…”
Section: Discussionmentioning
confidence: 60%